Political intervention in the Philippine bureaucracy, 1987 to 2010: How, where and to what effect - Toby C. Monsod (University of the Philippines, School of Economics (UPSE), 2015)
The act of increasing the number and penetration of presidential appointees in the bureaucracy is referred to as politicization. While politicization can be a short-term strategy for improving agency performance, it has been argued that politicization erodes the civil service corps in fundamental ways even when selected appointees are of consistently high quality [Lewis 2008]. Motivated by the continuing discussion on 'good governance' and how it can or should be pursued in the Philippines, this essay revisits the theme of political intervention in the bureaucracy by using updated sources of data to understand how politicization occurs, where it occurs and to what effect across five presidential terms from 1987 to 2010.
Keywords: 330